(In)dependence of elderly people at their home in performing basic activities of daily living - Silvana Sidney Costa Santos; Daiane Porto Gautério; Danielle Adriane Silveira Vidal; Bibiane Moura da Rosa; Bruna Zortea; Bianca Silveira Urquia (Universidade Federal do Ceará, 2013)
We aimed to outline the (in)dependence in performing basic activities of daily living of elderly people at home; apply educational geronto-technology to minimize specific functional loss; identify functional changes of these people, after using educational geronto-technology. This is a descriptive quantitative research, carried out in Rio Grande-RS, Brazil, with 109 elderly in three stages, from February 2011 to April 2012, using structured interview and the Katz Index. Data were grouped for statistical/descriptive treatment. First stage: female (69.7%), aged 60-69 years (43.0%), married (42.2%). Second stage: applying educational geronto-technology. Third stage: profile similarity of elderly people regarding the first stage. In performing basic activities of daily living, 21% of the elderly presented some dependence in the two data collections, highlighting the (urinary) continence function. Nurses need to understand the functional assessment of the elderly as a guiding tool for the planning and implementation of care.